The Tulip Tree - Rigsby, Howard (New York Doubleday and comp., 1963)
In this contemporary novel of romantic suspense, an old Hudson Valley house with a mysterious and violent history has a haunting impact on the young couple, Josephine and Kimball Watts, who are its new owners. Under the strain, Josephine and Kimball find their marriage endangered, and as events bring on a crisis, it seems that the dark spirit of the house will win over all who are under its spell.
Keywords: Fiction